Features of Hybrid Identity of the Second/Third Generation of European Muslims - Larisa A. Andreeva (Современная Европа)
The article deals with the problem of the hybrid identity of the representatives of the second/third generation of European Muslims, which has become a consequence of the failure of various strategies for the integration of migrants into European society. Hybridity arises in situations of cultural intersection when somewhat contradictory meanings and logics emanating from separate spheres of action combine to form new patterns. The article shows that a significant part of the representatives of the second/third generation of European Muslims, to one degree or another, accepts the collective European socio-cultural context (primarily, the values of secondary socialization), but at the same time expresses time preferences determined by religion, which are little compatible with European values. This reveals important characteristics of the hybrid identity of European Muslims ‒ ambivalence, multilayeredness and incompleteness. The study emphasises that the majority of representatives of the second/third generation of migrants do not identify themselves either through the nationality of their parents or through European identity, but recognise themselves through religious identity. Thus, religious affiliation is stronger than both identities. The main source of formation of the hybrid identity of second/third migrants is the conflict between religious self-identification and secular European identity. It is religion that is one of the restraining barriers to the integration of migrants into the secular European society. Similarly, the mobilization of religious identity underlies the formation of a hybrid identity of European Muslims of the second/third generations.